THE STUDY OF HYPOGLYCEMIC ACTIVITY OF 3-BENZYL-8-METHYLXANTHINE DERIVATIVES - I. М. Bilay; K. V. Aleksandrova; S. V. Levich; O. S. Shkoda; E. O. Michayluk; D. M. Yurchenko; D. M. Danilchenko (Zaporozhye State Medical University, 2015)
Diabetes mellitus is a chronic endocrine disease. It etiology is the impact of both endogenous (genetic) and exogenous factors that cause absolute or relative shortage of insulin or not effective use of it, which in turn leads to disruption of all kinds of substances exchange. The study of this problem is actual due to the high prevalence of diabetes, chronic disease, the tendency to increase the number of patients, their high morbidity and mortality. Diabetes is characterized by high blood glucose levels, which eventually leads to various complications associated with many human systems damage. Hormones (insulin and its analogues) and synthetic drugs (sulfonylureas, biguanides etc.) are used For the treatment of diabetes, but their high toxicity, cumulativeness, various side effects (autoimmunization, cutaneous allergic reactions, disturbance of the micro flora of the digestive tract), and the formation of insulin resistance restrict the use of these drugs in clinical practice. On this aspect the attention of researchers is attracted to xanthine derivatives, which are known as substances with wide range of biological activities including hypoglycemic. Based on the above, the search and development of new drugs among new 3-R-substituted xanthine, which would have hypoglycemic effect and would be deprived of most side effects is an acute problem of modern medical and pharmaceutical sciences. The aim of this study was to investigate the hypoglycemic activity of newly synthesized derivatives of 3-benzyl-8-methylxanthine and establish certain patterns "structure-activity" relationship. Materials and methods As objects of study for hypoglycemic activity we used derivatives of 3-benzyl-8-methylxanthine synthesized at the Department of Biochemistry and LaboratoryDiagnostics ofZaporizhzhyaStateMedicalUniversity. Hypoglycemic action of xanthine derivatives evaluated by intraperitoneal glucose tolerance test, which was reproduced by injection to animals (white rats weighing 160-230 g) glucose at a dose of 2 g/kg. The experimental animals were divided in 14 groups of 7 animals in each: 1. Intact - animals administered saline; 2. Control - modeling hyperglycemia without treatment. 3-13. Animals were injected xanthine derivatives at the background of hyperglycemia modeling. 14. The animals were injected metformin at the background of hyperglycemia modeling. We determined glucose level in blood using a glucometer «Accu Chek Active» after 30 and 60 minutes. Research results processed by modern methods of analysis using Student t-test. We used the level of statistical significance of differences of research results - p<0.05. Results and their discussion Presence of methyl and benzyl group or acetate residue at position 7 of xanthine bicycle resulted in incresing of glycemia in the blood of experimental animals. Replacing carboxyl hydroxyl to propoxy group or adding naphtylmethyl substituent reduced glycemia (compound 8 and compound 3) after 30 min glucose injection. Conclusions As a result of the research it was found that most hypoglycemic activity among the compounds that were studied, has 3-benzyl-7-(2-naphtylmethyl)-8-metylxanthine. Obtained results can be used in further searching of potential biologically active substances with hypoglycemic properties among derivatives of 3-benzylxanhine.